Anti-β2 glycoprotein domain 1 antibody as a diagnostic marker for antiphospholipid syndrome and a predictor of thrombosis: a systematic review and meta-analysis - Li, Linhui; Chen, Jian; Feng, Jing; Zhao, Hong; Liu, Xiaojuan; Jiang, Yongmei (Frontiers in Immunology, 2025)
Anti-β2 glycoprotein I domain 1 (anti-β2GPI-D1) antibodies have shown promise as diagnostic and prognostic markers for antiphospholipid syndrome (APS), but their clinical significance remains uncertain. This systematic review and meta-analysis evaluated the diagnostic accuracy of anti-β2GPI-D1 for APS and its association with thrombotic risk. A comprehensive search was conducted across PubMed, Web of Science, and Embase up to July 18, 2024. Eighteen studies (2,060 APS patients and 3,013 controls) were included in the diagnostic analysis, revealing a pooled sensitivity of 52% (95% CI 46%-58%) and specificity of 95% (95% CI 88%-98%). Anti-β2GPI-D1 demonstrated strong diagnostic value in distinguishing APS from other autoimmune diseases and healthy individuals, though its utility in differentiating APS from aPL carriers was limited. Additionally, five prospective cohort studies (210 APS patients, 430 aPL carriers, and 42 SLE patients) showed that anti-β2GPI-D1 was associated with an increased risk of thrombosis (pooled RR 1.75, 95% CI 1.07-2.87). Our findings suggest that anti-β2GPI-D1 offers high specificity and moderate sensitivity for APS diagnosis and may serve as a predictor of thrombosis.